NATURAL GAS HYDRATE: EFFECT OF SODIUM CHLORIDE ON THE CO2 REPLACEMENT PROCESS - Alberto Maria Gambelli; Mirko Filipponi; Andrea Nicolini; Federico Rossi (SGEM International Multidisciplinary Scientific GeoConference EXPO Proceedings, 19th International Multidisciplinary Scientific GeoConference SGEM2019, Energy and Clean Technologies, 2019)
Natural gas hydrate are solid compounds formed from water (host) and gas molecules (guest) at relatively high pressure and low temperatures. They are considered as a potential alternative energy source because of their high energy density, potential carbon-neutral nature and wide existence, both in permafrost and ocean seabeds. The most developed strategies for exploiting hydrate deposits are depressurization, thermal stimulation, chemical inhibitors and CO2 replacement. In particular, chemical inhibitors promote the NGH phase equilibrium curve shifting to higher pressure and lower, leaving the NGHs unstable in the local thermodynamic conditions. In the present work we proposed an analysis of how the present of salt affects the hydrate formation process, involving two different gaseous species: methane and carbon dioxide. If the inhibitor effect of salt on hydrate is well known, there are not enough information about the dependence of the inhibitor effect from the chemical species contained into hydrate. If CO2 and CH4 hydrate behaviour is different in presence of marine salt, their equilibrium curves might be nearer or farther in function of the salt concentration in correspondence of the hydrate deposit. A greater distance between these two curves could make the CO2 replacement process easier, less expensive and more efficient.